2003
DOI: 10.1161/01.str.0000063374.89732.9f
|View full text |Cite
|
Sign up to set email alerts
|

Constraint-Induced Movement Therapy and Rehabilitation Exercises Lessen Motor Deficits and Volume of Brain Injury After Striatal Hemorrhagic Stroke in Rats

Abstract: Background and Purpose-Constraint-induced movement therapy (CIMT) promotes motor recovery after occlusive stroke in humans, but its efficacy after intracerebral hemorrhage (ICH) has not been investigated clinically or in the laboratory. In this study we tested whether CIMT and a rehabilitation exercise program would lessen motor deficits after ICH in rats. Methods-Rats were subjected to striatal ICH (via infusion of collagenase) or sham stroke. Seven days later, treatment began with CIMT (8 h/d of ipsilateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(117 citation statements)
references
References 36 publications
2
112
3
Order By: Relevance
“…Even though collagenase does not discriminate among different brain tissues, it produces massive bleeding and mortality, similar to that in human ICH. This model has been used extensively in investigations of ICH (Brown et al, 1995;DeBow et al, 2003;Del Bigio et al, 1996;Elger et al, 1994;Lyden et al, 1997;MacLellan et al, 2002;Matsushita et al, 2000;Rosenberg and Navratil, 1997;Rosenberg et al, 1992), including studies on the long-term deficits after collagenase-induced ICH (Chesney et al, 1995). Another animal model used to determine ICH pathophysiology and to evaluate therapeutic treatment (Andaluz et al, 2002) is the direct injection of autologous blood into the rat caudate nucleus (Nath et al, 1986), a model used in numerous studies (Bullock et al, 1984;Huang et al, 2002;Jiang et al, 2002;Mendelow, 1993;Nath et al, 1987;Thulborn et al, 1990;Xue and Del Bigio, 2000;Wu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Even though collagenase does not discriminate among different brain tissues, it produces massive bleeding and mortality, similar to that in human ICH. This model has been used extensively in investigations of ICH (Brown et al, 1995;DeBow et al, 2003;Del Bigio et al, 1996;Elger et al, 1994;Lyden et al, 1997;MacLellan et al, 2002;Matsushita et al, 2000;Rosenberg and Navratil, 1997;Rosenberg et al, 1992), including studies on the long-term deficits after collagenase-induced ICH (Chesney et al, 1995). Another animal model used to determine ICH pathophysiology and to evaluate therapeutic treatment (Andaluz et al, 2002) is the direct injection of autologous blood into the rat caudate nucleus (Nath et al, 1986), a model used in numerous studies (Bullock et al, 1984;Huang et al, 2002;Jiang et al, 2002;Mendelow, 1993;Nath et al, 1987;Thulborn et al, 1990;Xue and Del Bigio, 2000;Wu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Acta Pharmacologica Sinica npg limb, functional recovery could be promoted [7] . Moreover, exposure of rats to task-specific [7,31,32] or nonspecific [10,[33][34][35][36] forelimb activity post-ischemia can improve functional outcomes.…”
Section: Wwwchinapharcom Livingston-thomas Jm Et Almentioning
confidence: 99%
“…Moreover, exposure of rats to task-specific [7,31,32] or nonspecific [10,[33][34][35][36] forelimb activity post-ischemia can improve functional outcomes. Notably, some experimental models of forced limb use in rodents have resulted in increased damage and worsened functional recovery [8,[37][38][39] .…”
Section: Wwwchinapharcom Livingston-thomas Jm Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…It is reasonable to expect that secondary degeneration of neurons might be attenuated by intense behavioral demand if the early vulnerable period is avoided. Indeed, a recent report of rats sustaining striatal hemorrhage indicated that a daily regimen of exercise, alternating with intermittent immobilization of the nonimpaired forelimb beginning 8 days after the initial insult, rescued neurons from delayed chronic degeneration [47]. It is very difficult to know, without unbiased stereological analysis of many regions of the brain at multiple time points, whether a motor treatment is optimally beneficial.…”
Section: Behavioral Modulation Of Neural Repair Mechanismsmentioning
confidence: 99%